Manufacturing Sector Performance - Zefanya Riyanto; Michael Ferdinan Sudirja (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study conducts a systematic review of literature on the determinants of banking performance, covering both financial and non-financial perspectives in conventional and Islamic banking. Using the PRISMA-based Systematic Literature Review (SLR) method, 15 key articles from 2015 to 2024 were analyzed. Findings show that indicators such as ROA, CAR, and LDR remain dominant, while organizational culture, workforce diversity, and Islamic values are gaining attention. However, most studies use cross-sectional data and focus on large national banks. Inconsistencies were noted in the effects of innovation and zakat. This study highlights the need for a multidimensional approach that integrates financial and non-financial factors to build an inclusive and sustainable banking performance evaluation model.